2017
DOI: 10.1186/s13075-016-1206-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimal regimens of sulfamethoxazole-trimethoprim for chemoprophylaxis of Pneumocystis pneumonia in patients with systemic rheumatic diseases: results from a non-blinded, randomized controlled trial

Abstract: BackgroundSulfamethoxazole-trimethoprim (SMX/TMP) is a standard drug for the prophylaxis of Pneumocystis pneumonia (PJP) in immunosuppressed patients with systemic rheumatic diseases, but is sometimes discontinued due to adverse events (AEs). The objective of this non-blinded, randomized, 52-week non-inferiority trial was to quest an effective chemoprophylaxis regimen for PJP with a low drug discontinuation rate. Results at week 24 were reported.MethodsAdult patients with systemic rheumatic diseases who starte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 41 publications
3
33
0
1
Order By: Relevance
“…PCP non-IRs at week 24 between SS and ES (the primary endpoint of this study) and the other comparisons between groups at week 24 have been reported previously [ 17 ]. The PCP non-IRs, treatment discontinuation rates and AEs at 52 weeks are reported here.…”
Section: Methodssupporting
confidence: 58%
See 3 more Smart Citations
“…PCP non-IRs at week 24 between SS and ES (the primary endpoint of this study) and the other comparisons between groups at week 24 have been reported previously [ 17 ]. The PCP non-IRs, treatment discontinuation rates and AEs at 52 weeks are reported here.…”
Section: Methodssupporting
confidence: 58%
“…The inclusion and exclusion criteria of the present study were described previously [ 17 ]. In brief, the inclusion criteria were follows: age ≥20 years; admission to one of the participating institutions for treatment of new-onset or relapsed systemic rheumatic disease in the study period; written informed consent; an oral prednisolone starting dosage at ≥0.6 mg/kg/day or an equivalent dosage of CS regardless of concomitant immunosuppressive drugs; no previous use of SMX/TMP, pentamidine isethionate or dapsone; and serum creatinine values within the upper limit of the normal range according to the institutional standard.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The implementation of a physical exercise program (resistance or aerobic physical training or the combination of these two) seems to be safe and beneficial in adult patients with SAM and should be used as a complement to pharmacological treatments in all stages of the disease to maximize muscle performance and aerobic capacity, as well as minimize the risk of side effects caused by GC treatment, for example. Individuals with active disease indication of physical exercises should preferably be instituted as early as possible and be supervised by a physiotherapist in close collaboration with an attending physician to strengthen the muscle groups involved with passive and active exercises (degree of recommendation B) for pneumocystosis should be considered, particularly in the presence of risk factors (e.g., interstitial lung diseases -ILD, other immunosuppressive drugs, patients with anti-MDA-5), for patients who use ≥20 mg/day of prednisone or its equivalent for a period of more than four weeks (B) [19,20] (D) [21] (C) [22][23][24].…”
Section: How Long Should Sam Patients Receive Immunosuppressive / Immmentioning
confidence: 99%